The Influence of Audit Committee Effectiveness on Banks’ Performance in Yemen - Al-Matari, Yahya Ali; Homaid, Abdo Ali; Alaaraj, Hassan (International Journal of Economics and Financial Issues, 2016)
This study aims at examining the effect of audit committee effectiveness characteristics namely, the frequency of meeting between audit committee and internal auditors, audit committee reviews of the internal audit proposals and audit committee reviews of the internal audit results on the performance of the bank’s performance. The study utilized a survey questionnaire method targeting 20 banks operating in Yemen. The result of the study was based on 112 usable questionnaires. The findings showed that there is a significant relationship between the three audit committee effectiveness characteristics and the performance of banks. Review of literatures concerning the audit committee characteristics used in this study are presented, the practical implications and the suggestions for future research works are also highlighted. Keywords: Corporate governance, internal audit, audit committee, banks’ performance, Yemen JEL Classifications: G21, M4